Self-assessment the competencies of surgical and critical area nurses. A cross-sectional study - Magro, Gaia; Dellai, Marisa; Notarnicola, Ippolito (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: This study aims to measure the competencies of surgical and critical area nurses, and to compare the nurses’ involved competencies in relation to the area to which they belongMethods: A cross-sectional study. The study was based on a convenience sample. The registered nurses were recruited from a hospital of the Friuli Western Health Authority. The Italian version of the Nurse Competence Scale composed from 58 items and validated in Italy in 2018 as a self-assessment tool for nursing competencies in the surgical and critical area, was self-administrated in October- November 2020.Results: The average competence level was found to be 68.7, with a median of 70 and a standard deviation of 19.7. The nurses felt more competent belongs to “Management of the care process”, specifically in “Recognizing critical situations for the patient's life early” (82.0). Most deficient was found in “Raising problems to be deepened with research” (50.9).Conclusions: The study found that nurses perceive a good level of competence with differences related to care settings. The results obtained from the study can provide nurses with the opportunity to reflect on their behaviours and periodically evaluate their knowledge and competencies, to promote professional development and continuing education. (www.actabiomedica.it)